Raising and Transparency - Langacker, Ronald W (Language (Baltimore), 1995)
An account of the phenomena that transformational syntax handled by means of "raising" is formulated in the context of cognitive grammar. Raising is analyzed as a special case of the metonymy that relational expressions exhibit in regard to their choice of overtly coded arguments. The transparency of these constructions is explained. (83 references) (Author/CK)